2015
DOI: 10.1590/s0102-67202015nahead00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Periods of Gastric Ischaemia in the Viability of the Tissue of Body, Fundus and Antrum Region of Rabbit Stomach

Abstract: BACKGROUND: Despite the rich vascular arcade of the stomach, gastric ischemia represents an important medical challenge and can be the consequence of obstructive or non-obstructive vascular processes of pathological or iatrogenic origin. AIM: To assess the effects of acute gastric ischaemia on the different regions of the stomach. METHOD: Fifteen New Zeland rabbits were divided into three groups: group 1, animals were observed during 3 h; group 2, during 6 h; group 3, during 12 h. Rabbit stomachs were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Polyps fundic gland, red streaks and normal mucosal appearance correlate with the negativity of HP infection as other studies 7 , 10 , 29 , but such associations could not be here demonstrated when analyzing the confidence interval obtained. With the selective collection of fragments for histological study in the supposedly positive cases 5 , 6 , 9 , 12 it avoids the routine submission for pathology in cases of morphological patterns not related to infection and with HP negative urease test.…”
Section: Discussionmentioning
confidence: 99%
“…Polyps fundic gland, red streaks and normal mucosal appearance correlate with the negativity of HP infection as other studies 7 , 10 , 29 , but such associations could not be here demonstrated when analyzing the confidence interval obtained. With the selective collection of fragments for histological study in the supposedly positive cases 5 , 6 , 9 , 12 it avoids the routine submission for pathology in cases of morphological patterns not related to infection and with HP negative urease test.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of gastric devascularization on the vitality of the stomach have been evaluated in few experimental studies 3,4 . In humans, partial stomach devascularization is used in the treatment of hypertension of gastric varices, acute hemorrhagic lesions of the gastroduodenal mucosa and also can be observed in cases of venous thrombosis, phlebitis and coagulopathies are predisposing factors of ischemia 4 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…The other is when the stomach is used in retrosternal position to preserve the digestive tube when an obstructed esophagus cannot be removed. In both instances, the vitality of the stomach is preserved only by right gastroepiploic vessels, the last branch and affluents of the gastroduodenal vessels [1][2][3][4] .…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…During ischemia there is Na + /K + pump failure, Ca 2+ influx, acidic substances formation, promoting endothelial injury, increasing permeability of the microcirculation and tissue edema that activates inflammatory response 13 . However, tissue damage is not limited to ischemia.…”
Section: Introductionmentioning
confidence: 99%